Influencer advertising on TikTok: advert formats and illicit product advertising. A study involving Germany, France, Spain and Italy - Rebeca Suárez-Álvarez; Ana Pastor-Rodríguez (Communication & Society (Formerly Comunicación y Sociedad), 2023)
Advertising by influencers on YouTube and Instagram has become a common practice, which includes the incorporation of advertising into their audio-visual productions as well. This study is being conducted to determine whether TikTok users from Germany, France, Spain, and Italy are using the social network to advertise products and services, and whether they are promoting products that are banned by TikTok. Using content analysis, 320 videos from 16 European tiktokers in Germany, France, Spain and Italy have been studied based on gender and nationality. The tiktokers ranged between 17 and 21 years of age with more than one million followers. The results confirm that tiktokers maintain a balance between the content they post and the advertising they insert. Both genders include a similar percentage of advertising and, based on nationality, French and Spanish tiktokers are the ones who use the most advertising in their work. Product placement is the most popular format for tiktokers of both genders in France, Spain and Germany, whereas branded content is preferred by Italian male tiktokers. None of the tiktokers of the four nationalities have violated the rules imposed by TikTok, as they have refrained from publishing illicit or dangerous products, either because of measures being taken by the social network itself to limit the exposure to these types of products, or as the result of self-regulation by the tiktokers in order to avoid being removed from the social network.